The Developmental Course of Parental Time Investments in Children from Infancy to Late Adolescence - Jocelyn Wikle; Clara Cullen (Social Sciences, 2023)
This study evaluated parent-child time from a child’s infancy to age 18 for mothers and fathers. Parent-child time remains a key input in child development. The theory on intergenerational transfers from parents to children posits that mother-child time and father-child time may adjust as children grow. This study used the nationally representative American Time Use Survey (2003–2019; N = 148,576) to study children ages 0–18 in a pooled cross-sectional sample. Using least squares regression, the study traced out parent-child contact, playing time, quality time, and one-on-one time, and tested differences between mothers and fathers. Mothers and fathers have provided substantial time investments in children of all ages. When children were young, mothers spent more time with children compared to fathers, highlighting a need for more nuanced discussions about differences in parenting between mothers and fathers. One-on-one time remained stable through late childhood and adolescence as parents prioritized focused interactions as children aged.